The First Catalog of Archaeomagnetic Directions From Israel With 4,000 Years of Geomagnetic Secular Variations - Shaar, Ron; Hassul, Erez; Raphael, Kate; Ebert, Yael; Segal, Yael; Eden, Ittai; Vaknin, Yoav; Marco, Shmuel; Nowaczyk, Norbert R.; Chauvin, Annick; Agnon, Amotz (Frontiers in Earth Science, 2018)
The large and well-studied archaeological record of Israel offers a unique opportunity for collecting high resolution archaeomagnetic data from the past several millennia. Here, we initiate the first catalog of archaeomagnetic directions from Israel, with data covering the past four millennia. The catalog consists of 76 directions, of which 47 fulfill quality selection criteria with Fisher precision parameter (k) ≥ 60, 95% cone of confidence (α95) < 6° and number of specimens per site (n) ≥ 8. The new catalog complements our published paleointensity data from the Levant and enables testing the hypothesis of a regional geomagnetic anomaly in the Levant during the Iron Age proposed by Shaar et al. (2016, 2017). Most of the archaeomagnetic directions show < 15° angular deviations from an axial dipole field. However, we observe in the tenth and ninth century BCE short intervals with field directions that are 19°-22° different from an axial dipole field and inclinations that are 20°-22° steeper than an axial dipole field. The beginning of the first millennium BCE is also characterized with fast secular variation rates. The new catalog provides additional support to the Levantine Iron Age Anomaly hypothesis.